2018
DOI: 10.3897/bdj.6.e27427
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms (Oligochaeta: Lumbricidae) of Interior Alaska

Abstract: Earthworms in the family Lumbricidae in Alaska, which are known from coastal regions, primarily in south-central and south-eastern Alaska, are thought to be entirely non-native and have been shown to negatively impact previously earthworm-free ecosystems in study regions outside of Alaska. Despite occasional collections by curious citizens, there had not been a standardised earthworm survey performed in Interior Alaska and no published records exist of earthworms species from this region. Mustard extraction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…have been found (utilizing the mineral soil as a habitat) in the arctic biome (purple shading) divided into three major geographical zones (sub-, low-, and high-arctic). Sites are compiled from previously published studies 27,47,49,[52][53][54][55] and findings presented in the Global Biodiversity Information Facility database. Red rectangle indicates a reported finding of L. rubellus in Greenland where the specific site was not reported 56 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have been found (utilizing the mineral soil as a habitat) in the arctic biome (purple shading) divided into three major geographical zones (sub-, low-, and high-arctic). Sites are compiled from previously published studies 27,47,49,[52][53][54][55] and findings presented in the Global Biodiversity Information Facility database. Red rectangle indicates a reported finding of L. rubellus in Greenland where the specific site was not reported 56 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to permafrost thaw, where effects are generated at greater soil depths and thus primarily affect deep-rooted plants 46 , geoengineering earthworms affect nutrient cycling within the upper few decimeters of soil where most plants have already allocated their roots. That geoengineering earthworms survive in discontinuous permafrost zones of Scandinavia, Russia, and North America when introduced by humans 27,[47][48][49] , shows that suitable habitats already exist in the Arctic, and highlight that their lagged northward dispersal needs to be considered when fully understanding long-term nutrient cycling at high latitudes. The demonstrated strong effects on the tundra plant N uptake by geoengineering earthworms show that natural or human-aided dispersal of novel, large detritivores into tundra soils can have substantial impacts on the tundra ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Conform to these findings, the distinct genetic composition of populations in Alberta and Minnesota correlated with the continental climate in both transects. However, both species were recorded from areas with harsh frost conditions (Booysen et al, ; Wackett et al, ). These areas were associated with recent human introductions and human land use indicating potential new stepping stones of earthworm invasions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, earthworms are susceptible to prolonged freezing periods, drought and geographic barriers like mountain ranges and large water bodies, which usually restrict their natural dispersal pattern (Eggleton, Inward, Smith, Jones, & Sherlock, 2009;Reynolds, 1994). However, they recently were recorded from interior Alaska and Fennoscandia suggesting that they can also withstand very low temperatures (Booysen, Sikes, Bowser, & Andrews, 2018;Wackett, Yoo, Olofsson, & Klaminder, 2018). Active dispersal of earthworms is slow, but they were able to spread across northern North America within a few hundred years by passive dispersal or repeated introductions, and today they are present in large areas from the east coast to the Midwest, east of the Rocky Mountains in Canada, and the Pacific coast (Hale et al, 2005;Holdsworth, Frelich, & Reich, 2007;Reynolds, 1977Reynolds, , 1994Reynolds, , 2016Reynolds, Linden, & Hale, 2002;Scheu & Parkinson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in North America also reported exotic earthworms in boreal forests (Alaska: Saltmarsh et al 2016;Booysen et al 2018). The most frequent exotic species observed in the Canadian boreal forest were D. octaedra (n = 84), A. tuberculata (n = 48), and L. rubellus (n = 44), which represent approximately 55% of all the specimens observed.…”
Section: Direct Detection: Observations Of Earthwormsmentioning
confidence: 69%